The circuit designer's companion - Williams, Tim, 1954- (Elsevier : Newnes, 2005)
Tim Williams' Circuit Designer's Companion provides a unique masterclass in practical electronic design that draws on his considerable experience as a consultant and design engineer. As well as introducing key areas of design with insider's knowledge, Tim focuses on the art of designing circuits so that every production model will perform its specified function and no other unwanted function - reliably over its lifetime. The combination of design alchemy and awareness of commercial and manufacturing factors makes this an essential companion for the professional electronics designer. Topics covered include analog and digital circuits, component types, power supplies and printed circuit board design. The second edition includes new material on microcontrollers, surface mount processes, power semiconductors and interfaces, bringing this classic work up to date for a new generation of designers. A unique masterclass in the design of optimized, reliable electronic circuits Beyond the lab - a guide to electronic design for production, where cost-effective design is imperative Tips and know-how provide a whole education for the novice, with something to offer the most seasoned professional.
Previous edition: 1991.
Keywords: Electronic circuit design.; elektronické knihy; electronic books